Keselamatan Dan Kesehatan Kerja Pada Offshore Wind Farm GEO QUIP MARINE Company - Ilham Okta Pratama; Sri Sundari; Marisi Pakpahan (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Quantitative research design with the subject of work safety and occupational health in offshore wind farms at GEO QUIP MARINE. Research method for collecting data using a questionnaire survey as research. This analysis shows that work safety and health hazards for marine geotech workers greatly influence work at this company and provide positive goals for the progress of this company. As the wind power sector grows and becomes an established source of renewable energy, it introduces new materials, technologies and processes that expose workers to increased and unique occupational risks. In this paper, we conducted an overview of the scientific and industrial literature on online scientific databases and search engines to identify the extent to which occupational health hazards and risks specific to wind power generation have been considered. Our review reveals the importance of work safety and the introduction of work safety tools at offshore wind farms such as PPE, H2S, and other equipment that influence offshore work maintenance is the focus of research, mainly including self-reported data from offshore wind farm employees. Factors such as vibration, welding fumes and other hazardous substances, weather conditions and biological hazards have not been addressed by research, although the presence and combination of these factors may raise concerns. Therefore, further research is needed into the unique and combined risks and hazards faced by workers across all stages of the wind energy production life cycle. This will increase knowledge and provide opportunities to manage occupational health and safety hazards in existing and newly built installations as well as provide input for future regulations and other preventative measures.